Disruptive Mood Dysregulation Disorder and its Ayurvedic Management - A Case Report (AYUSHDHARA, 2023)
Disruptive Mood Dysregulation Disorder (DMDD) is a condition in which children or adolescents experience ongoing irritability, anger, and frequent, intense temper outbursts. The symptoms of DMDD go beyond a “bad mood.” DMDD symptoms are severe. Youth who have DMDD experience significant problems at home, school, and often with peers. They also tend to have high rates of health care service use, hospitalization, and school suspension, and are more likely to develop other mood disorders. The present case of a 13 year old girl has worsening of mood characterized by irritability, anger, harming parent, crying spells, poor self care, social withdrawal for 12 months. The symptoms were increasing progressively and which badly affected her daily routine activities and school life. Here had never been a distinct period lasting more than one day during which the full symptom criteria, for a manic, hypomanic or a depressive episode had been met. In Ayurveda, the condition was diagnosed as Vathaja Unmada with Pithanubandha based on the symptoms of irritability anger etc. The treatment protocol including Snehapana, Virechana, Vasthi and Nasya was administered. During the treatment period family therapy methods also administered. After the intervention the symptoms were improved.